A Na3V2(PO4)2O1.6F1.4 Cathode of Zn‐Ion Battery Enabled by a Water‐in‐Bisalt Electrolyte. (12th July 2020) - Ni, Qiao; Jiang, Heng; Sandstrom, Sean; Bai, Ying; Ren, Haixia; Wu, Xianyong; Guo, Qiubo; Yu, Dongxu; Wu, Chuan; Ji, Xiulei
Abstract: Aqueous zinc‐ion batteries are receiving increasing attention; however, the development of high‐voltage cathodes is limited by the narrow voltage window of conventional aqueous electrolytes. Herein, it is reported that Na3 V2 (PO4 )2 O1.6 F1.4 exhibits the excellent performance, optimal to date, among polyanion cathode materials in a novel neutral water‐in‐bisalts electrolyte of 25 m ZnCl2 + 5 m NH4 Cl. It delivers a reversible capacity of 155 mAh g −1 at 50 mA g −1, a high average operating potential of ≈1.46 V, and stable cyclability of 7000 cycles at 2 A g −1 . Abstract : A hybrid‐valence vanadium compound of Na3 V2 (PO4 )2 O1.6 F1.4 is investigated as a Zn hosting cathode. Thanks to the neutral "water‐in‐bisalts" electrolyte comprising 25 m ZnCl2 + 5 m NH4 Cl, the Na3 V2 (PO4 )2 O1.6 F1.4 || Zn cell provides an alternative for aqueous zinc ion batteries with high voltage and long cyclability.